An Electromembrane Extraction with Polymeric Membrane under Constant Current for the Recovery of Cr(VI) from Industrial Water - Onaç, Canan; Kaya, A.; Sener, I.; Alpoguz, H. K. (The Electrochemical Society, 2018)
In this work, we performed EME experiments under a constant direct electric current with PIM. The method not only offered working opportunities with very low potential values (50-70 V), but also highlighted the suitability of PIM applications under constant current in EME. The donor solution is containing the target analyte while in the right chamber there is an acceptor solution to transport the target analyte. Cr(VI) transported from sample solution to an acceptor solution with a high efficiency and recovery 99.75% in 50 minutes. We worked applied electric current constant, platinum wire thickness, membrane stability and life through EME-PIM process, selectivity and applicability of EME-PIM process to the real samples. The Scanning Electron Microscopy also used to elucidate the morphology and structure of PIMs. The membrane's stability and the EME's reproducibility greatly improved by using a constant electric current instead of constant voltage, which can further lower transport times and enhance economical aspects of large-scale applications. © 2018 The Electrochemical Society.
Keywords: Large-scale applications; Chromium compounds; Electromembrane extractions; Reproducibilities; Industrial water; Direct electric currents; Electric currents; Morphology and structures; Economical aspects; Membrane stability; Scanning electron microscopy